Particle manipulation using dielectrophoresis with microelectrode array - Ling, Siang Hooi. (2013)
Dielectrophoresis (DEP) has been established as a promising particle manipulation technology. This technology is advantageous for the manipulation of various dielectric particles, and could be integrated relatively easily into a portable microfluidic device. In DEP particle manipulation, dielectric particles experience translational motions as a result of the interaction between the induced dipole in the particles with a non-uniform electric field. With different particles experiencing different dielectrophoretic forces, and in conjunction with a flowing medium, particle separation could be achieved. One of the DEP applications has provided a non-staining method to separate rare circulating tumor cells (CTCs) from blood samples, which is important to allow early cancer detection and may provide a minimally invasive method to monitor the results of cancer therapy. This serves as an alternative to other antibody-dependent cell separation methods such as immunomagnetic separation technique and fluorescent-activated cell sorting technique. At such, cells processed by DEP technique is advantageous for tissue engineering applications and cell molecular characterization study, owing to their functionality being unaffected when compares to antibody-dependent cell discrimination technique that requires specific antibody binding with the cell surface antigen. In this investigation, a continuous DEP separation methodology employing a novel electrode design is proposed and studied. The electrode design consists of a periodic array of discrete bottom microelectrodes and a continuous top electrode. With this design, continuous separation of polystyrene microspheres and biological cells as they traverse the microelectrode array can be achieved by the manipulation of the dielectrophoretic and the hydrodynamic Stokes forces. Unlike the conventional DEP technique which requires retention of one type of particles in order to separate the others, this methodology achieves separation and transportation of particle in a single continuous operation. In addition, unlike the IDEP technique employing protruded structures that are potential obstacles in obstructing the free flow of particles, the employed electrode configuration allows free flowing of particles across the embedded microelectrodes. In terms of ease of fabrication, the discrete bottom microelectrodes can be easily created by selectively removing areas of the insulator layer to expose the underlying indium tin oxide (ITO) conductive base. This fabrication approach is not only simple when compared to other microelectrodes created through a costly metal sputtering process, but it also provides a robust electrode design with a minimum risk of broken electrical circuit to each discrete microelectrode with the use of a continuous conductor, i.e. the underlying ITO conductive base.